Biology learning innovation: KIT "EGCA" based on sustainable development goals by problem-based learning model in global warming sub-matter - Jonathan Wahyu Triswidiyanto; Marisa Christina Tapilouw; Sucahyo Sucahyo (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Learning innovation is a form of learning development, such as teaching media development. One of the Sustainable Development Goals (SDGs), namely climate action, is introduced through the ecosystem and environmental change sub-material of global warming in grade 10. At SMA Kristen 1 Salatiga, learning global warming material has not used KIT (Integrated Instrument Components) learning media and problem-based learning models. This research aims to develop KIT "EGCA" media and test its effectiveness. This is an R&D (Research and Development) study with the 4D model (Define, Design, Development, Disseminate). Data analysis used media validity analysis and N-Gain Score to determine the improvement of learning outcomes (Pre-Post test). Based on the results of the study, most students are not familiar with SDGs, PBL, and KIT. The results of the validation test of KIT "EGCA" and learning modules obtained a very valid category, while the KIT "EGCA" instructions and student worksheets were valid. The results of the N-Gain calculation obtained a moderate category, which means that the developed product is effective. These results indicate that the "EGCA" KIT developed is valid and effective for use in learning. The implementation of KIT "EGCA" still needs to be optimized so that students are more familiar with SGDs, PBL, and KIT itself.Abstrak. Inovasi pembelajaran merupakan bentuk pengembangan pembelajaran, seperti pengembangan media pembelajaran. Salah satu tujuan Sustainable Development Goals (SDGs), yaitu climate action yang diperkenalkan melalui materi ekosistem dan perubahan lingkungan sub materi pemanasan global kelas 10. Pada SMA Kristen 1 Salatiga proses kegiatan pembelajaran materi pemanasan global belum menggunakan media pembelajaran KIT (Komponen Instrumen Terpadu) dan model pembelajaran berbasis masalah (Problem based learning). Tujuan penelitian ini yaitu mengembangkan media KIT “EGCA” dan menguji keefektifan media. Penelitian ini merupakan penelitian R&D (Research and development) dengan model 4D (Define, Design, Development, Disseminate. Analisis data yang digunakan analisis kevalidan media dan N-Gain Score untuk mengetahui peningkatan hasil belajar (Pre-Post test). Berdasarkan hasil penelitian, Sebagian besar peserta didik tidak familiar dengan SDGs, PBL, dan KIT. Hasil uji validasi KIT “EGCA” dan modul pembelajaran memperoleh kategori sangat valid, sedangkan instruksi KIT “EGCA” dan lembar kerja peserta didik valid. Hasil perhitungan N-Gain diperoleh kategori sedang, yang berarti produk yang dikembangkan efektif. Hasil ini menunjukkan KIT "EGCA" yang dikembangkan valid dan efektif digunakan dalam pembelajaran. Implementasi KIT "EGCA" masih perlu dioptimalkan agar peserta didik lebih familiar dengan SGDs, PBL, dan KIT itu sendiri.